Ecuación de estado cúbica para substancia pura usando los datos del segundo coeficiente del virial - de J, F. (Revista Mexicana de Física E, 2015)
In this work, a methodology to determine the cubic equation of state of a pure substance using experimental second virial coefficient data, the critical point, and the acentric factor, is described. For every cubic equation of state, the critical compressibility and the second virial coefficient are related through a restriction, which is shown and discussed. It was found that the restriction has important effects on the predictions of the thermodynamic properties (phase diagram) and the second virial coefiente of substance. From a cubic equation of state, the resulting predictions of thermodynamic properties and second virial coefficient cannot simultaneously describe the experimental data. This conclusion is derived from the numerical evidences.